2010
DOI: 10.1007/s10903-010-9424-7
|View full text |Cite
|
Sign up to set email alerts
|

Preconception Wellness: Differences in Health by Immigrant Status

Abstract: Disparities in health between immigrant and non-immigrant pregnant women in the United States is well documented, but few have documented disparities before pregnancy. Using the National Health and Nutrition Examination Survey (1999-2006), we examined the health of reproductive-aged women (8,095), sorted by immigrant and pregnancy pregnant US-born (P-US), pregnant foreign-born (P-FB), non-pregnant US-born (NP-US), and non-pregnant foreignborn (NP-FB). P-US women were 5.2 times more likely to report illicit dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
1
2
0
1
Order By: Relevance
“…This finding was surprising, as we had hypothesized that immigrant women hold more traditional views regarding birth control and also encounter more challenges accessing prescription contraception from their healthcare providers due to insurance and language barriers. Some previous findings [15,44], including Xaverius and Tenkku’s study, have supported the expected link between nativity and increased contraception use. However, their study was conducted in 1996–2006, when it may not have been as normative for FB women to use contraception.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…This finding was surprising, as we had hypothesized that immigrant women hold more traditional views regarding birth control and also encounter more challenges accessing prescription contraception from their healthcare providers due to insurance and language barriers. Some previous findings [15,44], including Xaverius and Tenkku’s study, have supported the expected link between nativity and increased contraception use. However, their study was conducted in 1996–2006, when it may not have been as normative for FB women to use contraception.…”
Section: Discussionsupporting
confidence: 58%
“…Foreign-born (FB) mothers, on average, have better overall health outcomes than US-born (USB) mothers despite facing adverse social and economic conditions in a new country; this phenomenon is referred to as the immigrant paradox or the Healthy Migrant Effect [12,13,14]. A hallmark study on preconception health by Xaverius and Tenkku (2012), which compared health behaviors among USB and FB non-pregnant women of reproductive age, showed that USB women were more likely than FB women to smoke, use illicit drugs, binge drink, be overweight/obese, engage in moderate physical activity and use contraception [15]. Further, examining birth outcomes by US nativity status adds further complexity to this picture.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, most FBHW come from very strict and hierarchal families where drugs and alcohol are seldom available to women. In these relatively protected communities, experimenting with alcohol drugs is severely punished and their consumption still has a very low level of social acceptance among the female immigrant community, regardless of their level of acculturation [49]. …”
Section: Discussionmentioning
confidence: 99%
“…En 2019, las mujeres representaron aproximadamente el 48% de la población mundial de migrantes internacionales de 272 millones. Estudios sobre la vivencia de mujeres migrantes evidencian profundas vulnerabilidades y desigualdades en la sociedad de acogida, lo que les genera tensión, inseguridad y desconfianza (Lacharité, 2005;Xaverius, Salas, & Tenkku, 2012), siendo insuficientes la toma de decisiones Revista Argentina de Ciencias del Comportamiento ISSN 1852-4206 Abril 2023 revistas.unc.edu.ar/inde x.php/racc…”
Section: Introductionunclassified